2013
DOI: 10.1111/joss.12024
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Measuring Adolescents' Perception of Complexity for Pictures of Fruit and Vegetable Mixes

Abstract: Complexity is an important parameter in the food industry because of its relationship with hedonic appreciation. However, difficulties are encountered when measuring complexity. The hypothesis of this study was that sensory descriptive analysis is an effective tool for deriving terms to measure adolescents' perception of complexity of pictures of fruit and vegetable mixes. A sensory panel evaluated 10 descriptive attributes, including simplicity and complexity, for 24 pictures of fruit and vegetable mixes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…However, out of the fourteen papers that investigated the relationship between complexity and hedonic responses, only one paper found an inverted U-curve relationship as suggested by Berlyne's theory. This paper investigated only the complexity of visual images (Mielby, Jensen, Edelenbos, & Thybo, 2013), which depends on factors like the size and number of different products, the number of different colors, and the type of color contrasts (Mielby, Kildegaard, Gabrielsen, Edelenbos, & Thybo, 2012). The other studies observed either positive, negative, or no relationships.…”
Section: Complexitymentioning
confidence: 99%
“…However, out of the fourteen papers that investigated the relationship between complexity and hedonic responses, only one paper found an inverted U-curve relationship as suggested by Berlyne's theory. This paper investigated only the complexity of visual images (Mielby, Jensen, Edelenbos, & Thybo, 2013), which depends on factors like the size and number of different products, the number of different colors, and the type of color contrasts (Mielby, Kildegaard, Gabrielsen, Edelenbos, & Thybo, 2012). The other studies observed either positive, negative, or no relationships.…”
Section: Complexitymentioning
confidence: 99%
“…Among these attributes, the collative properties defined by Berlyne (1967) were found of particular interest to study as it is hypothesized that local foods, in comparison to mainstream products, might carry a high level of surprising elements and high levels of complexity which might influence consumer liking. Complexity is understood as the inverse of simplicity (Mielby et al 2013). The appropriateness for use attributes were defined from the situations the consumers mentioned during the recruitment.…”
Section: Consumer Evaluationmentioning
confidence: 99%
“…Less work has been done on texture complexity (normally combined with flavor) (Bitnes, Ueland, Møller & Martens, 2009). For example, Weijzen, Zandstra, Alfieri & De Graaf (2008) selected four commercially available snacks which were "clearly different in taste and texture", and Mielby et al (2013) studied visual appearance complexity with mixed fruit images. Porcherot and Issanchou (1998), working with five experimental crackers varying in flavor but "identical in composition, shape and texture", asked consumers to score the crackers on a number of scales: Simple/Complex, Easy to describe/Difficult to describe, Composed of few ingredients/Composed of a lot of ingredients, and Mind few sensations/Mind a lot of sensations, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Complexity is not an easily defined concept. According to Mielby, Jensen, Edelenbos & Thybo (2013), problems often arise when trying to measure perceived complexity, as it can be difficult to know what is actually measured, especially since defining complexity is a hard task. A large part of the research on food complexity deals with different flavor stimuli (Kroeze, 1990;Schifferstein, 1992;Sunarharum, Williams & Smyth, 2014).…”
Section: Introductionmentioning
confidence: 99%